TASK-BASED LEARNING IN THE TEXTBOOK OF ENGLISH FOR PALESTINE - Rasha Sameer Karaki; Mohammed Abdul Hakim Farrah (University of Kuningan, 2019)
The aim of the study is to examine the ninth grade teachers' perceptions towards task-based learning (TBL) method and analyze the tasks and activities in the textbook of English for Palestine Ninth Grade. In addition, this study aims at evaluating the appropriateness and the effectiveness of TBL in the classroom. The researcher used four methods to collect data, namely questionnaire, classroom observation, interview, and content-analysis checklist. The sample of the study consisted of 185 teachers (males & females) from the government and UNRWA schools in Hebron District. The overall findings of the study revealed that the teachers perceptions towards TBL were positive and highly acceptable; they supported the effectiveness of communicative language teaching (CLT) and TBL in EFL classrooms. Then, the results of observational data showed that some teachers use new communicative methods for teaching language skills while others use the traditional ones. Meanwhile, the results of interviews indicated that the challenges of task-based learning were big-sized classes, length of material, lack of time, and lack of technological tools. The study ended with recommendations for syllabus designers, teachers, and students. It is recommended that the teaching and learning of English language skills at the Palestinian schools should be enhanced by the use of new flexible methods, such as TBL and communicative language teaching.